Gambaran multilokular ameloblastoma dengan pola soap-bubble dan kajian pustaka mengenai variasi gambaran radiografi ameloblastoma - Jatu Rachel Keshena; Aga Satria Nurrachman; Azhari Azhari (Ikatan Radiologi Kedokteran Gigi Indonesia, 2019)
Objectives: Ameloblastoma is classified as unicystic, multicystic and solid based on its characteristic. This article is aimed to report a case of ameloblastoma in posterior mandibula, analyze its radiographic appearance and emphasize on describing its other available variations. Case Report: A 39-years-old male patient came to Dadi Keluarga Hospital Purwokerto with complaint of swelling on the posterior lower jaw. The swelling was painless and has been felt since 4 years ago. Asymmetrical face was discovered. On panoramic radiograph, a well-defined radiolucent mass appears with radiopaque septation in the posterior region, the teeth were depressed, the lesion has expanded to the left coronoid process and mandibular notch. Conclusion: Based on panoramic radiographic examination the image of ameloblastoma in this case is seemed as multilocular in the posterior region, expanding to the left posterior and imaging of multilocular ameloblastoma on the left posterior region showing destruction of coronoid process and mandibular notch with soap-bubble pattern.